25-Hydroxylase vitamin D deficiency in 27 Saudi Arabian subjects: a clinical and molecular report on CYP2R1 mutations. Issue 7 (17th July 2021) - Bakhamis, Sarah; Imtiaz, Faiqa; Ramzan, Khushnooda; De Vol, Edward; Al-Sagheir, Osamah; Al-Rajhi, Abdulrahman; Alashwal, Abdullah; Bin Abbas, Bassam; Sakati, Nadia; Al-Sagheir, Afaf
Abstract : Vitamin D deficiency remains a major cause of rickets worldwide. Nutritional factors are the major cause and less commonly, inheritance causes. Recently, CYP2R1 has been reported as a major factor for 25-hydroxylation contributing to the inherited forms of vitamin D deficiency. We conducted a prospective cohort study at King Faisal Specialist Hospital & Research Centre, Riyadh, Saudi Arabia, to review cases with 25-hydroxylase deficiency and describe their clinical, biochemical, and molecular genetic features. We analyzed 27 patients from nine different families who presented with low 25-OH vitamin D and not responding to usual treatment. Genetic testing identified two mutations: c.367+1G>A (12/27 patients) and c.768dupT (15/27 patients), where 18 patients were homozygous for their identified mutation and 9 patients were heterozygous. Both groups had similar clinical manifestations ranging in severity, but none of the patients with the heterozygous mutation had hypocalcemic manifestations. Thirteen out of 18 homozygous patients and all the heterozygous patients responded to high doses of vitamin D treatment, but they regressed after decreasing the dose, requiring lifelong therapy. Five out of 18 homozygous patients required calcitriol to improve their biochemical data, whereas none of the heterozygous patients and patients who carried the c.367+1G>A mutation required calcitriol treatment. To date, this is the largest cohort series analyzing CYP2R1 -related 25-hydroxylase deficiency worldwide, supporting its major role in 25-hydroxylation of vitamin D. It is suggested that a higher percentage of CYP2R1 mutations might be found in the Saudi population. We believe that our study will help in the diagnosis, treatment, and prevention of similar cases in the future.